Effects of corncob derived xylooligosaccharide on innate immune response, disease resistance, and growth performance in Nile tilapia (Oreochromis niloticus) fingerlings - Hien Van Doan (2018)
© 2018 Elsevier B.V. An-eight week experiment was conducted to test efficacy of corncob derived xylooligosaccharides (CDXOS) on mucosal and serum immune, disease resistance, and growth performance of Nile tilapia (Oreochromis niloticus). Three hundred and twenty tilapia fingerlings (20.72 ± 0.02 g) were fed the following diets; 0 (Diet 1- control), added 5 – (Diet 2), 10 – (Diet 3), and 20 g kg−1CDXOS (Diet 4). After 4 and 8 weeks feeding were mucosal, serum immune responses, and growth performance measured. A challenge test (15 days) against Streptococcus agalactiae was conducted after 8 weeks post-feeding. A significant (P < 0.05) stimulation of skin mucus lysozyme and peroxidase activities, as well as serum immune parameters (serum lysozyme, serum peroxidase, alternative complement activities, phagocytosis index, and respiratory burst activity) was noticed by feeding the fish CDXOS supplemented diets compared to the control group. Highest (P < 0.05) innate immune parameters were observed by feeding the fish 10 g kg−1CDXOS vs. the other treatments. With regard to the challenge test, relative percent survival (RSP) of Nile tilapia fingerlings fed Diet 2, Diet 3, and Diet 4 was 34.78%, 60.87%, and 30.43%, respectively. Among the supplemented groups, dietary inclusion of 10 g kg−1CDXOS revealed significant (P < 0.05) higher RPS and resistance towards S. agalactiae than the other groups. Regarding growth performance, final weight, weight gain, specific growth rate, and feed conversion ratio were remarkably (P < 0.05) improved in the CDXOS groups; highest improvement was observed in the 10 g kg−1CDXOS treatment. In conclusion, inclusion of 10 g kg−1CDXOS derived from corncob improved growth performance and health status of Nile tilapia fingerlings.